2014
DOI: 10.1155/2014/713631
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton and Adhesion in Myogenesis

Abstract: The function of muscle is to contract, which means to exert force on a substrate. The adaptations required for skeletal muscle differentiation, from a prototypic cell, involve specialization of housekeeping cytoskeletal contracting and supporting systems into crystalline arrays of proteins. Here I discuss the changes that all three cytoskeletal systems (microfilaments, intermediate filaments, and microtubules) undergo through myogenesis. I also discuss their interaction, through the membrane, to extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 109 publications
0
21
0
Order By: Relevance
“…On the contrary, myoblasts grown within the Our study also found that the F-actin distribution differed noticeably between the 2D and 3D conditions. When H9c2 myoblasts cultured on 2D the substrates, the cortical actin filaments were localized close to the cell membrane, which is similar to precursor muscle cells (Costa, 2014). However, the actins distributed uniformly and occupied most of the cell cytoplasm when myoblasts were cultured within the 3D scaffolds.…”
mentioning
confidence: 66%
“…On the contrary, myoblasts grown within the Our study also found that the F-actin distribution differed noticeably between the 2D and 3D conditions. When H9c2 myoblasts cultured on 2D the substrates, the cortical actin filaments were localized close to the cell membrane, which is similar to precursor muscle cells (Costa, 2014). However, the actins distributed uniformly and occupied most of the cell cytoplasm when myoblasts were cultured within the 3D scaffolds.…”
mentioning
confidence: 66%
“…The cytoskeleton composed of microtubules, microfilaments (F-actin), and intermediate filaments [37] not only maintains the cell shape but also participates in cell proliferation and differentiation [36,38]. After incubation for 1, 4, and 24 h, no stress fibers, short ones in few cells, and distinct and long ones in the cells can be observed, respectively (Fig.…”
Section: Page 21 Of 43mentioning
confidence: 99%
“…Due to a great deal of research, each step in myogenesis has been studied and well characterized, particularly in cell cultures. 1 Unfortunately, cell cultures are adaptations that necessarily are different from the actual in vivo situation. Studies in cell cultures lack the structural and chemical complexity of the actual in vivo development.…”
Section: Introductionmentioning
confidence: 99%